The Effect of Business Mentoring, Business Model Innovation, and Social Media Use on Entrepreneurial Performance in Bogor - Chairul Hakim; Tera Lesmana; Supriandi Supriandi (West Science Interdisciplinary Studies, 2024)
Keywords: This research investigates the impact of business mentoring, business model innovation, and social media use on the entrepreneurial performance of small and medium enterprises (SMEs) in Bogor. Utilizing a quantitative approach, data were collected through surveys administered to 200 SMEs operating in various sectors. The study employs multiple regression analysis to assess the relationships between the independent variables (business mentoring, business model innovation, and social media use) and the dependent variable (entrepreneurial performance). The findings reveal that all three factors significantly and positively influence entrepreneurial performance. Business mentoring provides essential guidance and support, fostering skill development and strategic planning. Business model innovation encourages adaptability and competitiveness, leading to enhanced business outcomes. Social media use offers effective marketing channels and customer engagement, further driving business success. These insights underline the importance of comprehensive support systems for entrepreneurs, suggesting that policies promoting mentorship programs, innovation practices, and digital literacy can substantially benefit the SME sector in Bogor.